The determinants of house buyers' purchase decisions in Kota Bharu, Kelantan: a case of PMBK Development sdn. bhd. (PMBKD) / Nor Aliza Baharuddin, Puteri Nor Rhubiatul Adawiyah Mohd Zulkifli and Zarina Ismail - Baharuddin, Nor Aliza; Mohd Zulkifli, Puteri Nor Rhubiatul Adawiyah; Ismail, Zarina (2021)
The issue of unsold houses in Malaysia in recent years had became a serious concern to the housing developers. The total number of houses built exceeded the number of houses bought by the buyers led to the problems of unsold houses nationwide Therefore, there is a need to determine the factors that would influence potential house buyers to buy a house in order to understand this issue. Thus, the purpose of the study was to identify the determinants of house buyers' purchase decisions in Kota Bharu, Kelantan, a case of PMBK Development Sdn. Bhd. (PMBKD). Specifically, the study wants to investigate whether several variables such as quality, price, location, promotion, and corporate image are the factors that influence the house buyers' purchase decision when deciding to buy a house in Kota Bharu, Kelantan. Two (2) research objectives were outlined in order to answer the research questions that arose in this study; to examine the determinants of the purchase decision of house buyers when considering buying house in Kota Bharu, Kelantan and to recommend strategies that can be used by house developers to attract house buyers to buy. A total of 389 residents of Kota Bharu, Kelantan participated in this study through questionnaires distributed using Google Form format as the country was facing the Covid-19 pandemic that made face to face questionnaires distribution on the field quite impossible to execute. The study used SPPS Version 25.0 to analyze the data collected by the questionnaires. Before proceeding the data analysis, data screening and screening was conducted and this study found no missing values in the responses. In addition, the reliability test found that all items in the questions shown strong reliability and the test assumptions shown normality in the data and found no problems of homoscedasticity and multicollinearity. Consequently, this study used statistical tools such as correlations, and regression analysis to analyze the data in the SPSS. Based on the hypotheses testing and regression analysis, the result shows that only two (2) variables were positively significant in house buying decision (i.e. Location and Promotion). Several recommendations of strategies were made for PMBK Development Sdn. Bhd. (PMBKD) based on these findings so the company could come out with correct strategies to increase the sales of houses in the future. In a nutshell, this study managed to answer all the research objectives that were aimed.